Exploiting buck–boost duality in dual active bridge modular multilevel converters to achieve high DC step ratios. Issue 3 (23rd December 2020) - Kung, Sunny; Liu, Dalu; Perera, Chatumal; Haji, Moosa Moghimi; Salmon, John; Kish, Gregory
Abstract: A previously unidentified duality between buck and boost configured dc‐ac modular multilevel converters (MMCs) is firstly revealed. Armed with this insight, a new dual‐active‐bridge (DAB)‐MMC is proposed for high‐voltage dc (HVDC)‐to‐medium‐voltage dc (MVDC) power conversion that utilizes cascaded buck and boost dc–ac stages to obtain high dc step ratios. Single‐phase and three‐phase variants are presented. When compared with the conventional DAB‐MMC solution for the same dc step ratio, both the single‐phase and three‐phase topologies offer reduced MVDC side transformer winding current stresses, while the three‐phase topology also yields reduced MVDC side MMC submodule current stresses. The former is achieved by having the freedom to design the transformer with a lower turns ratio, and the latter is achieved due to the inherent paralleling of submodules on the MVDC side of the converter. Analysis of the three‐phase topology reveals its low‐voltage side transformer winding current stresses can be reduced by a factor of 3.27. A generalized mathematical model of the proposed buck–boost DAB‐MMC is derived and used to propose a dynamic controller for both the single‐phase and three‐phase topologies. Real‐time simulations obtained from a real‐time digital simulator system that incorporates an FPGA‐based controller for the valve firing controls validate the proposed buck–boost DAB‐MMC operation and dynamic controls.